Gamma-Aminobutyric Acid Transporters in the Nucleus Tractus Solitarii Regulate Inhibitory and Excitatory Synaptic Currents That Influence Cardiorespiratory Function - Martinez, Diana; Lima-Silveira, Ludmila; Matott, Michael P.; Hasser, Eileen M.; Kline, David D. (Frontiers in Physiology, 2022)
The brainstem nucleus tractus solitarii (nTS) processes and modulates the afferent arc of critical peripheral cardiorespiratory reflexes. Sensory afferents release glutamate to initiate the central component of these reflexes, and glutamate concentration is critically controlled by its removal via astrocytic neurotransmitter transporters. γ-aminobutyric acid (GABA) is the primary inhibitory neurotransmitter in the nTS providing tonic and phasic modulation of neuronal activity. GABA is removed from the extracellular space through GABA transporters (GATs), however, the role of GATs in nTS synaptic transmission and their influence on cardiorespiratory function is unknown. We hypothesized that GATs tonically restrain nTS inhibitory signaling and given the considerable nTS GABA-glutamate cross-talk, modify excitatory signaling and thus cardiorespiratory function. RT-PCR, immunoblot and immunohistochemistry showed expression of GAT-1 and GAT-3 mRNA and protein within the rat nTS, with GAT-3 greater than GAT-1, and GAT-3 colocalizing with astrocyte S100B. Recordings in rat nTS slices demonstrated GAT-3 block decreased spontaneous IPSC frequency and reduced IPSC amplitude evoked from electrical stimulation of the medial nTS. Block of GAT-3 also increased spontaneous EPSC frequency yet did not alter sensory afferent-evoked EPSC amplitude. Block of GAT-3 in the nTS of anesthetized rats increased mean arterial pressure, heart rate, sympathetic nerve activity, and minute phrenic nerve activity. These results demonstrate inhibitory and excitatory neurotransmission in the nTS is significantly modulated by endogenous GAT-3 to influence basal cardiorespiratory function.